Optimal treatment strategies for cT2 staged adenocarcinoma of the esophagus and the gastroesophageal junction: a multinational, high-volume center retrospective cohort analysis - Wirsik, Naita Maren; Kooij, Cezanne D.; Dempster, Niall; Crnovrsanin, Nerma; Donlon, Noel E.; Uzun, Eren; Bhanot, Kunal; Nienhüser, Henrik; Polette, Daniela; Kewani, Kammy; Grimminger, Peter; Reim, Daniel; et al. (Annals of surgery, 2024)
Objective: To evaluate outcomes after primary surgery (PS) or neoadjuvant treatment followed by surgery (NAT/S) in cT2 staged adenocarcinomas of the esophagus (EAC) and gastroesophageal junction (GEJ), a multinational high-volume center study was undertaken Background: The optimal treatment approach with either NAT/S or PS for clinically staged cT2cNany or cT2N0 EAC and GEJ remains unknown due to the lack of randomized controlled trials. Methods: A retrospective analysis of prospectively maintained databases from 10 centers was performed. Between January 2012 and August 2023, 645 patients who fulfilled inclusion criteria of GEJ Siewert type I, II, or EAC with cT2 status at diagnosis underwent PS or NAT/S with curative intent. The primary endpoint was overall survival (OS). Results: In the cT2cNany cohort, 192 patients (29.8%) underwent PS and 453 (70.2%) underwent NAT/S. In all cT2cN0 patients (n = 333), NAT/s remained the more frequent treatment (56.2%). Patients undergoing PS were in both cT2 cohorts older (P < 0.001) and had a higher American Society of Anesthesiologists classification (P < 0.05). R0 resection showed no differences between NAT/S and PS in both cT2 cohorts (P > 0.4). Median OS was 51.0 months in the PS group (95% CI: 31.6-70.4) versus 114.0 months (95% CI: 53.9-174.1) in the NAT/S group (P = 0.003) of cT2cNany patients. For cT2cN0 patients, NAT/S was associated with longer OS (P = 0.002) and disease-free survival (P = 0.001). After propensity score matching of the cT2N0 patients, survival benefit for NAT/S remained (P = 0.004). Histopathology showed that 38.1% of cT2cNany and 34.2% of cT2cN0 patients were understaged. Conclusions: Due to the unreliable identification of cT2N0 disease, all patients should be offered a multimodal therapeutic approach.
Gesehen am 24.06.2025